ANALYSIS OF FACTORS AFFECTING THE UNEMPLOYMENT RATE IN 10 DISTRICTS OF CENTRAL JAVA IN 2010-2017 - SE, Fredy Nashihin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
ABSTRACTThis study aims to analyze economic growth, inflation, total populationand poverty levels against the Open Unemployment Rate (TOT) in 10 Central Java Province Districts for 2010-2017. The data of this study are secondary data sourced from the Central Statistics Agency (BPS). The data analysis tool of this research is panel data regression. The results of this study indicate that the total population and the level of poverty have a positive and significant effect on open unemployment, meaning that the higher the population and the level of poverty, the open unemployment rate in 10 regencies in Central Java will increase. While economic growth has a negative but not significant effect on Open Unemployment. These results indicate that the increase in economic growth was not able to cause an increase in open unemployment in 10 districts in Central Java which became the object of this research. Conversely, if there is a decline or a slowdown in economic growth, then this also will not cause a decrease in the number of open unemployment in the area. Inflation variables have a positive but not significant effect on Open Unemployment. These results indicate that the increase in the total population is not able to cause an increase in open unemployment in 10 districts in Central Java which is the object of this research. Conversely, if there is a decrease in inflation, then this also will not cause a decrease in the number of open unemployment in the area.Â Keyword: Economic Growth, Inflation, Total population, Poverty LevelÂ